Synthesis and characterization of carbon nanotube aerogel from waste engine oil via floating catalyst chemical vapor deposition for oil spill removal - Abdullah, Hayder Baqer (2017)
Carbon nanotube (CNT) aerogel is a novel nanomaterial with three-dimensional (3D) macrostructure. The long CNTs assemble display high porosity, spinnability, structural stability, and good electrical conductivity. These characteristic represents a critical approach towards practical applications such as supercapacitors, gas storage, catalyst support, filtration, separation, biological sensors and oil spill removal. CNT aerogel is directly synthesized by floating catalyst chemical vapor deposition (FCCVD) using petrochemicals such as methane, cyclohexane, toluene or dichlorobenzene as a carbon source. Nevertheless, the high cost, depletion of the petrochemical products, and environmental aspects have brought the consideration of using waste engine oil (WEO) instead as a carbon source. This work is the first ever attempt to utilize WEO for CNT aerogel production. It was done via catalytic decomposition of WEO with ferrocene as a catalyst through FCCVD method. Prior to the reaction process, WEO was first filtered to remove dirt and any solid particles that might present. This was later followed by fractional distillation of the oil into different fractions which resulted in five (5) fractions. Gas chromatography-mass spectrometry (GC-MS) showed successful separation of low molecular weight hydrocarbons which was necessary for dissolving the catalyst, while Carbon-nitrogen-sulfur (CNS) analysis indicated that each fraction has more than 69% carbon, less than 0.2% nitrogen and less than 0.09% sulfur. The reaction was carried out at 1150 °C and 1200 °C in hydrogen with a flowing rate of 550 - 650 mL min-1. The carbon source solution (10 mL) was continuously injected into the furnace tube at a feeding rate of 10 mL h- 1 during one hour reaction time. It was found that all the synthesized CNT aerogel were multi-walled carbon nanotubes (MWCNTs) with 99.14% yield for CNT aerogel 3 synthesized at 1150 °C. Interestingly, CNT aerogel 2-2 and CNT aerogel 3-2 revealed graphenated carbon nanotubes (G-CNTs) structure obtained at reaction temperature 1200 °C. The CNT aerogels had a mesopore distribution with specific surface area in the range between 80.6 - 222.0 m2 g-1. Field emission scanning electron microscopy (FESEM) revealed randomly orientated to entangle thin multi-walled structure. Oil spill removal study was done by conducting benzene, toluene, and mxylene (BTX) as well as kerosene, diesel oil, palm oil and waste engine oil absorption of the synthesized CNTs. Results showed that CNT aerogel 5-2 gave the highest sorption capacity (Qe) for kerosene in both oil and oil/water system at 71.43 and 75.19 (g g-1), respectively. Absorption capacity was sustained at 90% for benzene, toluene, and m-xylene, 93% for kerosene, 87% for diesel fuel, 68% for palm oil, and 65% for waste engine oil even after 10 absorption cycles. Therefore, it can be concluded that CNT aerogel were successfully prepared from WEO by using FCCVD method which produced MWCNT at 1150 °C and graphenated CNT aerogel at 1200 °C. The CNT aerogel showed an excellent sorption capacity for all tested solvents and oils in both oil and oil/water systems with commendable recycle performance.